Problems of Overcoming Market Failures in the Context of Economic Crisis in the Euro Area - A. Y. Pluiko (Vestnik MGIMO-Universiteta, 2014)
The article analyses the manifestations of a market failure problem revealed during the economic crisis in the euro area, namely business cycles, market inability to ensure money circulation and avoid inflation. It is shown that the cyclicity of economic development has revealed in various degrees of economic contraction and different rates of its recovery. These differences have been exacerbated by the new procyclical factors emerged from the transition to a single currency. As for money circulation the crisis has almost no impact on the single currency functioning: the euro has maintained its position on the world market and properly performed money functions in the domestic. The goal to achieve economic development without inflation in the euro area generally has been solved successfully by the European Central Bank (ECB). However, due to the fact that the ECB in its monetary policy does not pay sufficient attention to the increased inflation in small and relatively poor countries, the crisis has been more acute in them than in large countries with low inflation. The goals of ensuring money circulation and avoiding inflation can be settled more effectively in the euro area in case of more tight coherence in economic policy and strengthening of supranational mechanisms of economic governance.